Potential use of the life satisfaction approach to value nonmarket goods and services - Cheryl Joy Fernandez; David Raitzer; Edimon Ginting (Asian Development Bank (ADB), 2019)
Economic analysis often faces challenges in the valuation of nonmarket goods and services. The traditional set of nonmarket valuation tools for measuring Marshallian economic surplus has limitations related to potential bias in stated preferences and endogeneity of nonmarket amenity placement in revealed preference studies. The life satisfaction approach offers a Hicksian compensating variationbased alternative, which uses self-reported subjective well-being to calculate the marginal rate of substitution of income for nonmarket amenities or services. The conceptual basis for the approach is explained and illustrated with an example from Iloilo, Philippines. Recommendations are offered for future application of the technique in the economic analysis of investment projects.
Keywords: D61; D69; D90; H40; Q51; 330; economic analysis; life satisfaction; natural disasters; Philippines; valuation; well-being